Happiness Permissibility: Negotiating Hadith on Polygamy as Perfection of Worship in Wahdah Islamiyah Muslim Women - Husain, Rahmin Talib; Abd. Hamid Wahid; Mahbub Ghozali; Zumiyati Sanu Ibrahim; Misbahuddin Asaad (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2024)
The practice of polygamy, which is debated among women, is accepted by Wahdah Islamiyah Muslim women as an embodiment of religious teachings enshrined in the hadith. This acceptance does not negate the complexities and contradictions inherent in the hadith that discuss the practice. This study explores the reading position of Wahdah Islamiyah Muslim women in understanding and practicing the hadith of polygamy. Using qualitative methods, data were collected through in-depth interviews with 12 persons consisting of 5 first wives, 5 second wives, 1 da’īyah (preacher), and 1 head of the Wahdah Islamiyah Muslim women. In-depth observations were also made of key informant activities. The data were analyzed using a fiqh (Islamic Jurisprudence) analysis model combined with the framework of Stuart Hall's reception theory. The findings of this study reveal three different reading positions: 1) The hegemonic reading model using the argument of belief in an authoritative text. 2) the negotiated reading model emphasizing the fulfillment of the husband's needs driven by concerns about the husband's compliance with the principles of justice. 3) the oppositional reading model rooted in the vulnerability of wives who challenge of ensuring fair treatment. These three positions emerge from the structure of the hadith discourse where the textual affirmation of polygamy serves as the basis for its resolution. The incorporation of settlement in an interpretive and counterintuitive perspective in the development of fiqh signifies a full acceptance of the law while also considering the goals of responsible individuals (maqāṣid al-mukallafīn).